Designing A Sustainable Business Model Using BMC, SWOT, and TLBMC to Strengthen Biomass Supply Chain Resilience in Indonesia - Lestari, Purbo; Pujawan, I Nyoman (Riviera Publishing, 2025)
Indonesia's energy transition is accelerating the integration of biomass through co-firing in coal-fired power plants (PLTU), with a national target of 10 million tons of biomass utilization by 2025. However, supply inconsistency, quality variability, and logistical inefficiencies remain key obstacles. This study aims to develop a sustainable business model for a local biomass supplier by integrating the Triple Layered Business Model Canvas (TLBMC), Value Proposition Canvas (VPC), and SWOT analysis. This qualitative research adopts a case study design, with data collected through in-depth interviews, field observations, and document analysis. Informants include internal stakeholders from the supplier, state-owned electricity entities, and related institutional actors. The analysis identifies strategic strengths and weaknesses of the current model, external opportunities and threats, as well as gaps in quality control, dependency on external partners, and insufficient integration of environmental and social dimensions. By constructing a modified TLBMC–VPC framework based on SWOT findings, the study proposes a more resilient and efficient business model aligned with national decarbonization goals and inclusive supply chain engagement. The results contribute to enhancing supplier readiness and improving strategic alignment with Indonesia’s low-carbon energy transition agenda.